Peran Perencanaan dan Pengorganisasian dalam Meningkatkan Kualitas Pembelajaran di Sekolah - Fania, Fira; Siska, Mery (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Planning and organizing play a very important role in the effective and efficient achievement of educational goals. Good planning in the world of education involves identifying clear educational goals, developing appropriate strategies to achieve them, as well as preparing detailed activity plans to ensure all available resources are used optimally. With careful planning, every educational activity can be carried out with a clear direction and in accordance with the objectives that have been set. This research aims to examine the role of planning and organizing in improving the quality of learning in schools.Meanwhile, organizing is an important step in ensuring that the plans that have been prepared can run smoothly. Organizing in education includes dividing tasks, determining an appropriate organizational structure, and determining the roles and responsibilities of each individual in implementing the plan. Through effective organization, all elements in the education system, including teaching staff, students and other resources, can work together harmoniously to achieve the desired educational goals. This research uses normative research methods or doctrinal research where secondary data sources or library research will be used in this research, namely by examining secondary materials in the form of scientific books, journals, etc. Data analysis techniques use secondary materials or library research which are then analyzed and presented descriptively. The results of this research show that in the education system, the success of planning and organizing is greatly influenced by how well these two elements are implemented. In the context of education managed by both the private and state parties, good organization allows for optimal use of resources, which in turn will have a positive impact on the quality of education itself.